Molecular Dynamics Simulations of n-octyl-ÃŽÂ²-D-glycosides: Some Structural Properties of Micelles - Teow Chong, Teoh,; Hashim, Rauzah (Malaysian Journal of Science, 2003)
Micellar structures of n-octyl-β-D-maltopyranoside (OM) and n-octyl-β-D-glucopyranoside (OG) were investigated using molecular dynamics simulation. The gyration radii of OM and OG micelles were compared. In order to investigate the effect of head group, the micellar structure of n-octyl-β-D-gaIactopyranoside (Ogal) was also studied. It was found that OG formed bigger micelles with gyration radii ranging from 7.18 to 11.62Å. OM formed a small micelle with gyration radius of 8.21Å and Ogal formed miceiles with gyration radii ranging from 8.66 to 11.07Å.